Experiences with agricultural development in tropical Africa : volume 2, the case studies - De Wilde, John C.; World Bank. (Baltimore : Published for the International Bank for Reconstruction and Development by the Johns Hopkins Press, 1967)
The study discusses land tenure reform; agricultural extension and education; agricultural credit and; market organization in several districts of Kenya, as well as other African countries namely: Mali, Republic of Chad, Upper Volta, Ivory Coast, and Tanzania.
Includes bibliographical footnotes and index.
ne 03/09/2019
Loans
Keywords: Agriculture